Profesor y portafolio en la consolidación de una cultura de la evaluación-como-aprendizaje - Picón-Jácome, Edgar (Colombian Applied Linguistics Journal, 2021)
This article presents the results of a case study that explored the challenges of implementing an assessment portfolio in the EFL institutional program of a Colombian public university. The findings that resulted from the analysis of semi-structured interviews, focal groups, faculty meetings and teachers’ reflections permitted entering the day-to-day evaluative practices of the participants, selected through a purposeful sampling approach, and identifying dynamics, roles and conceptualizations related to the portfolio implementation. The data analysis disclosed positive washback both on the development of teacher and learner autonomy, derived from the exercise of a teachers’ reflective practice influenced by their role in the implementation of the portfolio. However, there was also evidence of practicality issues related to the time and experience demanded by a dialogic feedback integrated to the process vs. a focus on evaluating the product. Some teachers overcame this challenge through the use of ICT (Information and Communication Technologies) and the exchange of experiences. This revealed the importance of articulating teacher experience and ICT training to LAL (Language Assessment Literacies) programs.